Does Self-Sacrifice Make Me Great? Research on the Relationship Between Employee Conscientiousness and Pro-Social Rule Breaking - Liu, Xiayi; Wang, Hongqing; Liu, Xiajun (Frontiers in Psychology, 2022)
Based on the theory of purposeful work behavior, this study proposed that the two facets of employee conscientiousness, duty orientation and achievement orientation, have opposing effects on pro-social rule breaking (PSRB). We also explored how the critical task characteristic (job autonomy) and social characteristic (leader reward omission) of employees moderate the above relationships. Drawing on data from 216 two-stage employee surveys, we found that duty orientation positively predicts PSRB, while achievement orientation negatively predicts PSRB. Furthermore, job autonomy, by amplifying employees’ perceived meaningfulness of their higher-order implicit goals, can strengthen the positive effect of duty orientation and the negative effect of achievement orientation on PSRB. Similarly, leader reward omission could also activate the negative effect of achievement orientation and PSRB, but not significantly moderate the positive relationship between duty orientation and PSRB. By separating the distinct role of facet-specific personality, our study sheds light on the relationship between employee conscientiousness and PSRB.